1985
DOI: 10.1271/bbb1961.49.925
|View full text |Cite
|
Sign up to set email alerts
|

Chemical nature of a desmutagenic factor from burdock (Arctium lappa LINNE).

Abstract: Studies were carried out to elucidate the chemical nature of the desmutagenic factor of Burdock (Arctium lappa Linne), Which is shown to be a complex polymer having a molecular weight of about 300,000.5) Its desmutagenic effects are demonstrated on indirect mutagens such as Trp-P-1 and Trp-P-2, as well as on direct mutagens such as 2-nitro-l,4-diamino benzene and 4nitro-l,2-diamino benzene. The present findings suggest that this factor is not a protein because of the low content of nitrogen and the non-color r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0
1

Year Published

1993
1993
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 0 publications
0
9
0
1
Order By: Relevance
“…Most of the evidence is based on in vitro studies, however, few in vivo studies are reported and no clinical trials in the United States or Canada with the whole tonic have been conducted to date; however, preclinical and clinical trials on gastroenterology patients have been conducted by the Russian Ministry. Articles addressing the beneficial antimutagenic, anticarcinogenic, and antioxidant effects of several of the herbs have been published (Silver and Krantz, 1931;Ley and Reeve, 1997;Yang et al, 1997;Odin, 1997;Agarwal and Mukhtar, 1996;Dombradi and Foldeak, 1996;Foldeak and Dombradi, 1964;Morita et al, 1984Morita et al, , 1985Kimura et al, 1980;Maruta et al, 1995). Thus, the herbal mixture may have synergistic antitumour and immunostimulant activities since the individual herbs exhibit specific biological activity.…”
Section: Review Of Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the evidence is based on in vitro studies, however, few in vivo studies are reported and no clinical trials in the United States or Canada with the whole tonic have been conducted to date; however, preclinical and clinical trials on gastroenterology patients have been conducted by the Russian Ministry. Articles addressing the beneficial antimutagenic, anticarcinogenic, and antioxidant effects of several of the herbs have been published (Silver and Krantz, 1931;Ley and Reeve, 1997;Yang et al, 1997;Odin, 1997;Agarwal and Mukhtar, 1996;Dombradi and Foldeak, 1996;Foldeak and Dombradi, 1964;Morita et al, 1984Morita et al, , 1985Kimura et al, 1980;Maruta et al, 1995). Thus, the herbal mixture may have synergistic antitumour and immunostimulant activities since the individual herbs exhibit specific biological activity.…”
Section: Review Of Researchmentioning
confidence: 99%
“…In vitro studies demonstrated that the aqueous extract of burdock root decreased mutations in cells exposed to toxic chemicals (Morita et al, 1984). In addition, animals that consumed burdock root were protected against several toxic chemicals (Kimura et al, 1980;Dombradi and Foldeak, 1966;Foldeak and Dombradi, 1964;Morita et al, 1985). The anticarcinogenic activity of natural and synthetic flavonoids has been evaluated in mice.…”
Section: Mechanisms Of Action (A) Protection Against Cellular Damagementioning
confidence: 99%
“…species as antioxidant activity (12,13), and 2-nitro-1,4diaminobenzen was isolated as a desmutagenic compound (14). This plant has been used to study the physical dietary fibers (15).…”
mentioning
confidence: 99%
“…Analysis of its components and its desmutagenic effect have been reported (4,5). Few reports, however, have addressed the antioxidant activity of burdock.…”
mentioning
confidence: 99%